Anatomy of the Anterolateral Abdominal Wall Ultrasonographic Assessment and its Application as a Guide in Nerve Blocks (International Journal of Medical and Surgical Sciences, 2014)
The transversus abdominis plane (TAP) is the anatomical space between the internal oblique and transversus extends throughout the abdominal wall ending in the aponeurosis of rectus muscles. Anesthetic block of this plane has proven useful in reducing pain and analgesic requirements in abdominal wall surgery. The identification of anatomical structures by ultrasound images simplifies the procedure by correctly and safely blocking innervation of the abdominal wall with the use of local anesthetics. The aim of this study was to highlight the importance of anatomical knowledge, and correlation of anatomical-clinical-surgical and ultrasound information in the interpretation of images obtained by ultrasonography. Further, to evaluate the effects of nerve block of the anterolateral abdominal wall by echo-guided puncture in reference to the need for postoperative analgesia in abdominal surgery. During the period January / 2012 to June / 2013, we conducted training for surgeons through practical observation of normal anatomy on cadavers, ultrasound and observation of the anterolateral abdominal wall with portable ultrasound and 7 MHz linear transducer in patients with, and without known pathology, and then interpreted and compared these for a period of 6 months. Puncture sites for blocking nerve plexus were identified and located by ultrasonography. Following training we considered patients with comorbid conditions that were surgically treated. We included 60 patients underwent surgery for abdominal wall pathology. They were classified considering surgery performed: 14 (23.34) umbilical hernioplasties, 33 (55%) inguinal hernioplasties, 6 (10%), epigastric hernioplasties, 4 (6.66%) femoral hernioplasties and 3 (5%) other hernias. We were able to identify anatomical structures and nerve block in 30 (90.91%) patients underwent surgery for inguinal hernias and 3 (75%) femoral hernioplasties. In the remaining patients block could not be performed due to physical characteristics and when ultrasound equipment was not available: 1 (25%) with femoral hernia and in 3 (9.09%) inguinal hernias. No post-puncture complications were detected. A reduced need for analgesics was observed in all patients during the immediate and midrange post-operative period. Thorough knowledge of anatomical structures and nerve endings, as well as the use of this complementary approach, significantly improve the management of postoperative pain and reduce the need for analgesics. Training in ultrasound and surgical anatomical-clinical correlation to identify these structures should be considered to improve the quality of care in patients with abdominal surgical pathologies.